Implementasi Framework Laravel Pada Sistem Penyewaan Lapangan Futsal Menggunakan Metode Waterfall Di Global Sport Futsal - Ardiman, Andre; Feoh, Gerson; Ardiada, I Made Dwi (LPPM UNIKA Santo Thomas Medan, 2024)
The purpose of this research is to construct a web-based futsal court rental system at Global Sport Futsal using the Laravel framework and the Waterfall approach. This facility, which is situated on Jalan Mudutaki Dalung, now uses manual booking procedures, which causes problems including scheduling conflicts and inefficiencies. By allowing users to verify court availability and make appointments online, the proposed system seeks to expedite the reservation process by avoiding record-keeping mistakes and the necessity for in-person attendance. Features like cost computation, payment confirmation, real-time booking validation, and account registration are all included in the system. It is anticipated that the deployment of this computerized leasing system would improve operational effectiveness for Global Sport Futsal's clients as well as management.